Performance of Cryogenic Machining with Nitrogen Gas in Machining of Titanium - Thet, Thet Mon (Trans Tech Publications, 2011)

(untitled)
This research presents performance of nitrogen gas as a coolant in machining titanium. Compressed nitrogen gas stored in a cylindrical tank is supplied to the cutting zone via the stainless steel tube of 2x8x25mm (inside diameter x outside diameter x length) connected to the flexible hose and specially-designed valve with pressure controller. Machining experiments are carried out on conventional turning center. The cutting tool used is triangular insert of ISO-TPGN160308 with the holder (ISO-CTGPR3232K). The cutting insert grade is KC5010 (TiAlN3 coated carbide) as recommended by Kennametal for machining titanium. During machining, the tube is manually directed to be just-above the tool rake face and the nitrogen gas is supplied with high pressure so that the cutting zone receives an effective cooling as well as the chip brakes easily. The effectiveness of this new cooling strategy is demonstrated by the cutting edge condition and surface finish after machining at various speeds, and also by comparing with performance of conventional coolant. The result is found to be excellent in terms of relative amount of tool wear and surface finish. The cutting insert has surprisingly remained almost intact when using nitrogen gas coolant whereas severe tool wear occurred with conventional coolant even at low cutting speed. This cryogenic strategy also improved machined surface quality greatly.